2018
DOI: 10.1007/s13197-018-3190-2
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant potential and physicochemical characterization of yellow, purple and orange passion fruit

Abstract: This study evaluated yellow, purple and orange passion fruit in pulp, peel, and seed for physicochemical characteristics, proximate composition, minerals, antioxidant capacity (DPPH and ABTS), phenolic compounds, carotenoids, flavonoids and anthocyanins. Yellow passion fruit presented higher concentrations of pectin (37.37 g/100 g) in peels; high cryptoxanthin, α-carotene, β-carotene, provitamin A, quercetin, and kaempferol in pulps and higher values of ash and total dietary fiber in seeds. The purple fruit wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
70
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 28 publications
11
70
0
8
Order By: Relevance
“…In another study, Jiménez et al [14] identified cyanidin-3-O-β-D-glucopyranoside in a peel extract obtained with methanol acidified with acetic acid (19:1, v/v). The anthocyanins delphinidin-3,5-O-glucoside, cyanidin-3-O-glucoside and pelargonidin-3-O-glucoside, and the aglycones delphinidin and cyanidin were reported by Dos Reis et al [15] in purple passion fruit peel homogenized with acidified methanol (1% HCl).…”
Section: Anthocyanin Profile Of the Epicarp Extractmentioning
confidence: 80%
“…In another study, Jiménez et al [14] identified cyanidin-3-O-β-D-glucopyranoside in a peel extract obtained with methanol acidified with acetic acid (19:1, v/v). The anthocyanins delphinidin-3,5-O-glucoside, cyanidin-3-O-glucoside and pelargonidin-3-O-glucoside, and the aglycones delphinidin and cyanidin were reported by Dos Reis et al [15] in purple passion fruit peel homogenized with acidified methanol (1% HCl).…”
Section: Anthocyanin Profile Of the Epicarp Extractmentioning
confidence: 80%
“…We found (1!4)-linked galacturonic acid is the main component of polysaccharides from yellow and purple passion fruit. Diverse studies have demonstrated that pectin and fibers from P. edulis peel can effectively eliminate free radicals such as DPPH and ABTS (Dos Reis et al, 2018), reduce cholesterol and blood glucose levels (Lacerda-Miranda et al, 2016), and obviously inhibit the growth of sarcoma180 (Silva et al, 2012), and so forth. Thus, the passion fruit peel may be utilized in the development of new fiber-rich healthy food products.…”
Section: Pectin Fiber and Polysaccharidesmentioning
confidence: 99%
“…Expect for YNY and GXY, the level of vitexin was increased, and released amount was 4.22-11.97 μg/ml. Vitexin have been found in buckwheat in form of bound phenolics with low content (dos Reis, Facco, Salvador, et al, 2018). The increased vitexin may be caused by the release from the combined phenolics in passion fruit juices.…”
Section: Individual Phenolic Compounds Identificationmentioning
confidence: 99%